Workplace communication - Mikkola, Leena, 1969-; Valo, Maarit, 1953- (Routledge, Taylor & Francis Group, 2020)
This book provides insights into communication practices that enable efficient work, successful collaboration, and a functional work environment. Maintaining a productive and healthy workplace is predicated on interpersonal communication between people. In organizations, efficient communication is the foundation of all actions. Contributors to this book cover communication issues in relationships, teams, meetings, leadership, competence, diversity, organizational entry, social support, and digital environments in the workplace. The book illustrates all these issues in detail by presenting both relevant research findings and their practical implications in working life. Workplace Communication is ideal for current and future employees, directors, supervisors and managers, instructors, and consultants in knowledge-based expertise work. The book is appropriate for courses in organizational and leadership communication or interpersonal communication in a workplace setting.